(untitled) (Altre Modernità, 2024)
With the short story Der Hagestolz (1845), Adalbert Stifter reflects on the role of old age in the relationship between generations: on the one hand, the calm existence of elderly characters hides regrets for lost opportunities, on the other hand, the fears and intemperance of immaturity risk condemning the younger ones to inexorably lose themselves in the same mistakes as those who came before them. The encounter and exchange between the melancholic and gruff bachelor living his old age confined to an island and his rebellious nephew thus promote the need for a healthy dialogue for society as a whole, which is called upon to reconcile with history and learn about the past so as not to be trapped in its failures. The very structure of the work helps to recompose this relationship, starting from the failures and ruptures and ending with the pedagogical solution suggested by the author. Following the peculiar Stifterian conception, which sees the microcosm as a mirror of wider phenomena, this study aims to consider not only the facts and characters mentioned in the story, but to propose a broader contextualisation of Stifter’s message in the light of the historical dynamics that swept through the Habsburg periphery.